Comprehensive analysis pinpoints CCNA2 as a prognostic and immunological biomarker in non-small cell lung cancer - Liming Zhang; Shaoqiang Wang; Lina Wang (BMC Pulmonary Medicine)
Abstract Background Lung cancer is a leading cause of morbidity and mortality globally. Despite advances in targeted and immunotherapies, overall survival (OS) rates remain suboptimal. Cyclin-A2 (CCNA2), known for its upregulation in various tumors and role in tumorigenesis, has an undefined function in non-small cell lung cancer (NSCLC). Methods We analyzed three microarray datasets from the Gene Expression Omnibus (GEO) repository to identify differentially expressed genes. Using STRING, we constructed a protein-protein interaction (PPI) network to pinpoint hub genes. The expression and prognostic relevance of CCNA2 were validated using GEPIA and the Kaplan-Meier plotter. Clinicopathological correlations were assessed via the Human Protein Atlas (HPA) and UALCAN databases. qRT-PCR and immunohistochemistry (IHC) were performed to validate CCNA2 mRNA and protein levels. Loss-of-function assays in lung cancer cell lines evaluated the biological role of CCNA2. Immune infiltration and single-cell sequencing were also explored. Results Analysis of GSE18842, GSE101929, and GSE116959 datasets identified 321 upregulated and 623 downregulated genes in NSCLC. CCNA2 was confirmed to be highly expressed in NSCLC through qRT-PCR and IHC, with overexpression correlating with advanced pathological stages and lymph node metastasis. The area under the curve (AUC) of CCNA2 indicating high diagnostic accuracy. Immune infiltration and single-cell sequencing revealed that CCNA2 expression was significantly associated with immune cell infiltration, particularly in Tprolif cells. Conclusion CCNA2 is upregulated in NSCLC and shows significant correlation with clinicopathological characteristics. Our findings suggest that CCNA2 may serve as a promising biomarker for both the prognosis and diagnosis of NSCLC.